Redefinition of the genus Krczaldania Sasa, 1961 stat. nov. (Acari: Heterostigmata: Pygmephoroidea) with notes on its generic synonyms and redescription of Pygmephorus primitivus Krczal, 1959 - Alexandr A. Khaustov (Persian Journal of Acarology)
The subgenus Allositeroptes Livshits, Mitrofanov and Sharonov, 1986 of the genus Siteroptes Amerling (Acari: Pygmephoridae) is considered as junior synonym of Krczaldania Sasa, 1961 stat. nov. The subgenus Krczaldania Sasa, 1961 is redefined and elevated to a generic rank. The type species of the genus Krczaldania - Pygmephorus primitivus Krczal, 1959, is redescribed based on material from Crimea, Ukraine. A key to the known species of the genus Krczaldania is provided.